Continuous signals and systems with MATLAB® - Elali, Taan S. (CRC Press, Taylor & Francis Group, 2021)
"The book offers broad, detailed, and focused comprehensive coverage of continuous linear systems, based on basic mathematical principles. It presents many solved problems from various engineering disciplines using analytical tools as well as MATLAB. This book is intended primarily for undergraduate junior and senior electrical, mechanical, aeronautical, and aerospace engineering students. Practicing engineers will also find this book useful"- Resumé vydavatel
Keywords: MATLAB (software); zpracování signálů; systémová analýza; matematická optimalizace; signal processing; system analysis; mathematical optimization; učebnice vysokých škol; textbooks (higher)